ANALISIS PELAKSANAAN PROGRAM AMBULAN SIAGA KOTA SEMARANG TAHUN 2019 - Maudy Ritra Andini; Septo Pawelas Arso; Wulan Kusumastuti (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2020)
Indonesian government has made efforts to fulfill the community’s needs about health care. One of the innovation program was The Semarang City Alert Ambulance Program. This program aims to improve health degrees by easier the community having healthcare access. This study was conducted to determine the implementation of The Semarang City Alert Ambulance Program. The research was located in the postal territories of the Ngesrep Public Health Center. This was qualitative research with a descriptive approach using an in-depth interview method with purposive sampling. The analyzed variables were human resources, funds, facilities, SOP or policies, planning, organizational structure, implementation, evaluation, and environment. In input variables, the competency of human resources was good, but the number of human resources still not enough, the funding for the program execution was enough but the facilities still not enough yet, and the SOP has not been formed. Then, in the environment variable, there was no regulation to govern, it caused the implementation of this program interrupted. The Semarang City Government need making specific mayor rules related to the program. The Semarang Health Service needs making regulation and SOP, making ideal planning.